Biodiversity Benefits for Size Modulation of Metal Nanoparticles to Achieve In Situ Semi‐Oxidation toward Optimized Electrocatalytic Oxygen Evolution. (30th March 2022) - Zhang, Jia; Sun, Rong‐Zhi; Zhang, Xue‐Feng; Wu, Jun‐Xi; Dou, Yu‐Hai; Zhu, Xuan‐Yi; Yu, Li‐Hong; Guo, Lu‐Yao; Liu, Min‐Ling; Guo, Lin; Cao, Li‐Ming; He, Chun‐Ting; et al.
Abstract: Biodiversity endows similar species with subtle differences in composition, microstructure, and surface chemistry, making biomass a promising precursor to control the resulting active structure for heterocatalysis. Here, it is shown that Tremella fuciformis ( Tfu ), possessing an abundant porous structure and favorable metal affinity, is favorably serves as a precursor for confining uniform metal nanoparticles, by comparing the chemical characteristics of six varieties of agarics. The modest size of Co in the Tfu derived composite, Co@NPC‐ Tfu (NPC = N, P co‐doped carbon), is suitable for in situ semi‐oxidation during oxygen evolution reaction (OER), forming a stable core‐shell structure of Co3 O4 @Co. Thus, Co@NPC‐ Tfu can be used as a state‐of‐the‐art electrocatalyst for OER with an overpotential of 213.6 ± 4.1 mV at 10 mA cm −2, and a significant turnover frequency of 3.21 s −1 at 300 mV, benefitting from the optimum trade‐off between the atom utilization and electrical conductivity. Operando spectroscopy and theoretical calculations unveil the occupied state modulation of the robust carbon‐bonded PO x groups, which optimizes the intermediate adsorption to accelerate OER kinetics. Moreover, Tfu derived Ni@NPC‐ Tfu can be also prepared as a high‐performance hydrogen evolution reaction electrocatalyst, which can be utilized for efficient overall water splitting coupled with Co@NPC‐ Tfu . Abstract : Biodiversity is used to control the sizes of metal nanoparticles for resulting modest particle size to achieve in situ semi‐oxidation, forming a stable core‐shell nanostructure of Co3 O4 @Co supported by P‐doped carbon. The trade‐off between conductivity and atom utilization, as well as the carbon‐bonded PO x groups jointly promote electrocatalytic oxygen evolution reaction.